Public services in the digital age: A systematic review and bibliometric analysis of trends and challenges in digital governance - A. Ariyadi; M Akbar (Tamalanrea: Journal of Government and Development (JGD), 2025)
In the digital era, public services, governance, and civic engagement have undergone significant transformations driven by rapid technological advancements and evolving citizen expectations. To illustrate the emerging trends, challenges, and opportunities in digital governance, this study presents a comprehensive systematic literature review combined with quantitative bibliometric analysis. By integrating powerful bibliometric tools such as VOSviewer with rigorous systematic review methodology, this study identifies key issues and technological advancements shaping the evolving landscape of digital public administration. The findings reveal two sides of digitalization: while it significantly improves service efficiency, transparency, accountability, and citizen satisfaction, it simultaneously raises critical concerns related to cybersecurity threats, complex regulatory adaptation, digital inclusion gaps, and equity in access. To ensure a responsive, sustainable and inclusive digital transformation in public service delivery, this study emphasizes the urgent need for a coherent policy framework that supports robust digital infrastructure development, continuous capacity building of public officials, and enhanced multi-stakeholder collaboration among government, private sector, and civil society. The study also discusses practical implications and future research directions to support governments in navigating the complex digital governance environment effectively.